Proceedings of the 23rd Conference on Computational Natural Language Learning (CoNLL) 2019
DOI: 10.18653/v1/k19-1038
|View full text |Cite
|
Sign up to set email alerts
|

Automated Pyramid Summarization Evaluation

Abstract: Pyramid evaluation was developed to assess the content of paragraph length summaries of source texts. A pyramid lists the distinct units of content found in several reference summaries, weights content units by how many reference summaries they occur in, and produces three scores based on the weighted content of new summaries. We present an automated method that is more efficient, more transparent, and more complete than previous automated pyramid methods. It is tested on a new dataset of student summaries, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The automated wise crowd method performs fairly well on these summaries, as described in [64], with a Pearson correlation of 0.66 on the Autonomous Vehicle summaries when comparing the manual and automated summary content assessment, and a Pearson correlation of 0.72 for the Cryptocurrency summaries. Previously, the instructor found the content scores and justifications to be very useful, including cases where the tool gave low scores to written work that, on reflection, were scored favorably based on the writing fluency rather than the content [67].…”
Section: B Content Annotation and Analysis: The Wise Crowd Methodsmentioning
confidence: 79%
See 1 more Smart Citation
“…The automated wise crowd method performs fairly well on these summaries, as described in [64], with a Pearson correlation of 0.66 on the Autonomous Vehicle summaries when comparing the manual and automated summary content assessment, and a Pearson correlation of 0.72 for the Cryptocurrency summaries. Previously, the instructor found the content scores and justifications to be very useful, including cases where the tool gave low scores to written work that, on reflection, were scored favorably based on the writing fluency rather than the content [67].…”
Section: B Content Annotation and Analysis: The Wise Crowd Methodsmentioning
confidence: 79%
“…Originally this method was applied through manual annotation procedure (see next paragraph). An automated approach to the assessment and feedback step has been developed [62] and, more recently, a fully automated approach called PyrEval that identifies and ranks the SCUs from a set of reference summaries, then uses the weighted SCUs to assess new summaries [64], was developed. PyrEval was tested on summaries from the Autonomous Vehicles and Cryptocurrency topics.…”
Section: B Content Annotation and Analysis: The Wise Crowd Methodsmentioning
confidence: 99%
“…Originally, this method was applied through manual annotation procedure (see next paragraph). An automated approach to the assessment and feedback step was developed [57] and, more recently, a fully automated approach called PyrEval that identifies and ranks the SCUs from a set of reference summaries, then uses the weighted SCUs to assess new summaries [60]. PyrEval was tested on summaries from the AV and Cryptocurrency topics.…”
Section: B Technology For Supporting Experiential Learning 1) Content Annotation and Analysis (The Wise Crowd Method)mentioning
confidence: 99%
“…In this step, which uses SEAView, elementary discourse units (EDUs) are annotated [61], [62]; these are effectively individual clauses or propositions stored in the sep file. In contrast to a summary of a source text, the quality of a student's argument is not expected to depend on how much of The automated wise crowd method performs fairly well on these summaries, as described in [60], with a Pearson correlation of 0.66 on the autonomous vehicle summaries when comparing the manual and automated summary content assessment, and a Pearson correlation of 0.72 for the cryptocurrency summaries. In a previous study [63], the instructor found the content scores and justifications to be very useful in understanding cases where the tool gave lower scores to written work compared to those given by the tutors.…”
Section: B Technology For Supporting Experiential Learning 1) Content Annotation and Analysis (The Wise Crowd Method)mentioning
confidence: 99%
“…Recently, systems have been developed to ease the construction of Pyramid scores, e.g. (Hirao et al, 2018;Yang et al, 2016;Gao et al, 2019b;, but they still require human-annotated Summary Content Units (SCUs) to produce reliable scores. Besides SCUs, recent work has explored eliciting preferences over summaries (Zopf, 2018;Gao et al, 2018Gao et al, , 2019a and annotations of important bi-grams (P.V.S and Meyer, 2017) to derive summary ratings.…”
Section: Related Workmentioning
confidence: 99%